Acute ischemic stroke what is hidden behind?. Issue 5 (November 2017) - Alonso, Joaquín Valle; Martin, David; Kinderman, Harriet; Farhad, Islam; Swallow, Peter; Siggers, Aidan
Abstract: Acute aortic dissection (AAD) is a rare and potentially fatal disease. The classic presentation is sudden and severe pain in the chest, back, or abdomen, described as tearing or ripping pain radiating to the interscapular region. Cerebral ischemic complications occur in 18–30% of aortic dissections and patients may present to the emergency department (ED) with isolated focal neurology and no chest pain. In AAD patients, presenting with stroke and subsequently thrombolized, a 71% mortality rate has been reported in patients receiving recombinant tissue plasminogen activator (r-TPA). We present a case of a 58-year-old male patient that presented to ED with sudden onset of headache and left-sided hemiparesis, computed tomography (CT) demonstrated an ischemic stroke of the right middle cerebral artery. When the question of whether to start r-TPA or mechanical thrombectomy was discussed, a cardiac point-of-care ultrasound was performed in ED and showed a type A aortic dissection; immediately a CT aortic angiogram was performed and confirmed the diagnosis. The patient was taken to theater and had a favorable outcome. <Learning objective: Acute aortic dissection (AAD) may present as acute ischemic stroke with no chest pain. In patients with acute ischemic stroke with an unclear etiology point-of-care ultrasound (POCUS), cardiac, and aortic ultrasound are important rapidly to diagnose AAD and avoid the deleterious effect of thrombolysis. This case supports the feasibility of emergency physicians performing POCUS assessments for AAD.>